عمالة الأطفال وتأثيرها على الإستقرار الإجتماعي للطفل - عسبار لخضار (البليدة2- كلية العلوم الإنسانية و الإجتماعية, 2026)
حاولنا من خلال هذه الدراسة السوسيولوجية الميدانية الموسومة تحت عنوان "عمالة الأطفال وتأثيرها على الاستقرار الاجتماعي للطفل" تشخيص هذه الظاهرة وفق دراسة علمية موضوعية سوسيولوجية بغرض الوقوف على تأثير عمالة الأطفال على الاستقرار الاجتماعي للطفل. وعليه فإن الهدف الرئيسي لهذه الدراسة هو تسليط الضوء على عمالة الأطفال وتأثيرها النفسي والصحي والجسدي على الطفل، بالإضافة إلى كيفية تحولها من وسيلة للتدريب واكتساب المهارات إلى الولوج في عالم الانحراف، وكيف يساهم تقصير مؤسسات الضبط الاجتماعي في أداء دورها في زيادة إنتشار هذه الظاهرة. واعتمدت هذه الدراسة على المنهج الوصفي ودراسة الحالة وتحليل المحتوى وكذا شبكة الملاحظة والمقابلة في جمع معطيات الدراسة. This field study, titled "Child Labor and its Impact on the Child's Social Stability, aimed to diagnose this phenomenon through an objective, scientific sociological approach, specifically examining its effects on the child's social stability. The study's primary objective was to demonstrate the psychological, health, and physical impact of child labor on children. It also explored how child labor transforms from a means of training and skills acquisition into a path toward delinquency, and how the shortcomings of social control institutions contribute to the increased prevalence of child labor. This study employed a descriptive methodology, including case studies, content analysis, observation, and interviews to gather data. Our findings revealed that child labor negatively impacts a child's social stability due to its detrimental effects on their socialization and integration into society. Furthermore, we found that child labor, in a work environment lacking legal and familial oversight, transforms from a means of skills training into a vehicle for acquiring deviant behaviors. Children often begin to adopt deviant and unethical behaviors as necessary for adapting to the work environment. The shortcomings of social control institutions in their performance also contribute to the increased spread of the phenomenon of child labor.
Keywords: عمالة الأطفال; الإستقرار الإجتماعي للطفل; سوسيولوجيا الطفولة; مشكلات الطفولة